2016
DOI: 10.1111/obr.12475
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of specific lipid groups in serum of obese humans: a review

Abstract: Obesity is a major contributor to the dysfunction of liver, cardiac, pulmonary, endocrine and reproductive system, as well as a component of metabolic syndrome. Although development of obesity-related disorders is associated with lipid abnormalities, most previous studies dealing with the problem in question were limited to routinely determined parameters, such as serum concentrations of triacylglycerols, total cholesterol, low-density and high-density lipoprotein cholesterol. Many authors postulated to extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 305 publications
(563 reference statements)
5
72
1
3
Order By: Relevance
“…Our results showing increased serum levels of many different fatty acids in obese individuals are consistent with existing published reports . Similarly, serum fatty acid levels were elevated in obese asthma patients compared to nonobese asthma patients.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showing increased serum levels of many different fatty acids in obese individuals are consistent with existing published reports . Similarly, serum fatty acid levels were elevated in obese asthma patients compared to nonobese asthma patients.…”
Section: Discussionsupporting
confidence: 93%
“…In obese subjects, serum short-chain MUFAs and SFAs are positively correlated to inflammatory markers and C-reactive protein, while odd-chain and iso-branched chain SFAs showed inverse association (18). Eicosanoids are the products of n-3 and n-6 PUFAs, which include pro-inflammatory eicosanoid mediators from AA, whereas anti-inflammatory eicosanoid products are produced from the n-3 PUFAs (45).…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted within the European EPIC cohort has reported an association between high percentages of plasma phospholipid ITFAs and increased risk of weight gain during the follow-up, particularly in women (17). A recent review by Mika and Sledzinski (18) reported a trend for a positive association between obesity and serum SFAs, MUFAs, and TFAs, and a negative association for odd-chain and branched SFAs. Endogenous production of FAs through the desaturation activity influences the relative levels of individual S-PLFAs.…”
mentioning
confidence: 99%
“…Reports have suggested that excessive FAs might augment inflammation through activation of toll‐like receptor (TLR) signalling and following activation of nuclear factor kappa‐light‐chain enhancer of activated B‐cells (NF‐κB) . There is increasing evidence that FA availability is an independent predictor of metabolic disorders including insulin resistance and T2DM . It appears likely that FA accumulation results in increased levels of FA intermediates, such as long‐chain acylcarnitines, which underpin lipotoxic effects in heart mitochondria .…”
Section: Pathophysiology Of Disturbances In Mitochondrial Metabolism mentioning
confidence: 99%